2001
DOI: 10.1021/ma001852m
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Thermoreversible Gelation of Block and Star Copolymers of Poly(ethylene glycol) and Poly(N-isopropylacrylamide) of Varying Architectures

Abstract: We report the development of a new gelation mechanism and a new family of polymers that self-assembles to form gels in a thermoreversible fashion. The polymers are block or star copolymers with a central hydrophilic poly(ethylene glycol) (PEG) segment (A) and temperature responsive poly(Nisopropylacrylamide) (PNIPAAm) terminal segments (B). Copolymers of various architectures, AB, A(B) 2, A(B)4, and A(B)8, were synthesized to investigate the structures and properties relationship. At 5 °C, the viscosities of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
164
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(171 citation statements)
references
References 30 publications
7
164
0
Order By: Relevance
“…The formed solid was dissolved in distilled water to form 100 mg/ml solution and centrifuged 0.5 hour (10,000 rpm, Eppendorf 5415C) at 40°C to separate the unreacted PEO. Colorimetric analysis was carried out with Ce(IV) as a colorimetric reagent to verify that no unreacted PEO remained [11]. The precipitated copolymer products were dried under reduced pressure.…”
Section: Synthesismentioning
confidence: 99%
“…The formed solid was dissolved in distilled water to form 100 mg/ml solution and centrifuged 0.5 hour (10,000 rpm, Eppendorf 5415C) at 40°C to separate the unreacted PEO. Colorimetric analysis was carried out with Ce(IV) as a colorimetric reagent to verify that no unreacted PEO remained [11]. The precipitated copolymer products were dried under reduced pressure.…”
Section: Synthesismentioning
confidence: 99%
“…reported on linear and star-shaped block copolymers of PEO and PNiPAAm and found that (PEO-PNiPAAm) 4 showed a sol-gel transition to a strong gel at 37 °C and exhibited the highest moduli compared to the other polymers. 71 Fechler et.al. reported 4-arm stars with PEO inner blocks and P(DEGMA-co-OEGMA) outer blocks, which formed fully reversible free-standing hydrogels at 15 wt% upon heating.…”
mentioning
confidence: 99%
“…68 Second, using multi-arm (AB) x type copolymers lowers the critical gelation concentration by eliminating the micelle formation step. [69][70][71] This will be discussed below.…”
mentioning
confidence: 99%
“…In their experiments, they used a label (Lysosensor Green) that fluoresces more strongly in a lysosome or an endosome, where the pH is more acidic (about 4.8), compared to a pH of 7.1 outside these compartments (83,84). Flow cytometry was then used to analyze cells exposed to US and P105 micelles with Lysosensor Green.…”
Section: In Vitro Research and Mechanism Of Ultrasound-cell Interactionmentioning
confidence: 99%